Introduction to chemical engineering - Ghosal, S.K (Tata McGraw Hill Education Private Ltd., 2010)
Introduction to chemical engineering / Ghosal, S.K. -- New Delhi: Tata McGraw Hill Education Private Ltd., 2010 660 G411 No. of Copies : 1